2016
DOI: 10.3390/en9020078
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of Separators in Air-Breathing Flat-Plate Microbial Fuel Cells—Part 1: Structure, Properties, and Performance Correlations

Abstract: Passive air-breathing microbial fuel cells (MFCs) are a promising technology for energy recovery from wastewater and their performance is highly dependent on characteristics of the separator that isolates the anaerobic anode from the air-breathing cathode. The goal of the present work is to systematically study the separator characteristics and its effect on the performance of passive air-breathing flat-plate MFCs (FPMFCs). This was performed through characterization of structure, properties, and performance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Figure 15 shows examples of one-compartment MFCs. 78,79 Figure 13(c) Separator/electrode assembly 72 the electrolytes employed in MFCs have low conductivity, lowering the interelectrode spacing may result in lower internal resistance of batteries. 16 Bringing the electrodes too close together may result in oxygen diffusion at the anode, thus limiting the growth of bacteria that create electricity and possibly causing short circuits.…”
Section: Design Of Mfcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 15 shows examples of one-compartment MFCs. 78,79 Figure 13(c) Separator/electrode assembly 72 the electrolytes employed in MFCs have low conductivity, lowering the interelectrode spacing may result in lower internal resistance of batteries. 16 Bringing the electrodes too close together may result in oxygen diffusion at the anode, thus limiting the growth of bacteria that create electricity and possibly causing short circuits.…”
Section: Design Of Mfcsmentioning
confidence: 99%
“…The concentration of substrate also affects MFC performance, in addition to the substrate itself. A saturation-type relationship has been observed between the power generated and the amount of substrate originally fed to the reactor; 79 Cheng and Logan demonstrated that this parameter remarkably affected the anode's performance. 79 The findings of Khaled are summarized in Fig.…”
Section: Influence Of Substrate Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also designed a novel arrangement by totally replacing cathode graphite plates with a light (0.065 g), flexible, and cheap plastic membrane obtaining higher energy density than conventional PEMFCs. In the cathode design, they used the air-breathing concept (Figure 1), introduced in 2013 [92], and afterwards, intensely developed to make PEMFCs suitable to wearable devices [93]. Another important issue of this topic covers the choice of suitable oxygen reduction reaction (ORR) electrocatalysts, which are known to be key materials for efficient and highly performant PEM and Zn-airFC devices [82,84,94].…”
Section: Polymer Electrolyte and Zinc-air Fuel Cellmentioning
confidence: 99%
“…Exploded view of fuel cell components in an air-breathing configuration. Reproduced from reference[93] under CC BY 4.0 license.…”
mentioning
confidence: 99%